Seasonality and Pattern in Leaf-fall and Litter Accretion on the Forest Floor in Plantations of Demonstration Area, Forest Research Institute & colleges, Dehra Dun (India) - Pande, P. K.; Sharma, S. C. (Indian Forester, 1986)
The present study deals With the Patterns in leaf-fall, its seasonality and litter accretion in four plantations of sal, leak, pine, and eucalypts. The leaf-fall followed the order (in kg/hal sal (8286.21), eucalypts (9908.12), teak (5009.42) pine (4780.82) while tolal litter was in order of sal (11271.08> pine(9674.30) eucalypts (7069 .8) and teak. The variation in amounts of litter fall has been reasoned for evergreen, semi-evergreen and deciduous nature of the tree species as well as the density of the respective stand and associated tree species. A clear-cut pattern was observable in sal, with a maxima in leaf-fall during the months of March-April, while pine and teak showed during the months of April-May. Eucalypts recorded bimodal patterns of leaf-fall, one peak (22%) durinq october - November the other (18.8%) during April-May. The first peak supposed to be genetically determined and the second environmentally stressed. In conclusion it has been assumed that eucalypts plantations are unale to draw the advantage of their leaf-fall probably due to lag in time between the active growth of the plant and subsequent decomposition of the deposited leaf-fall and litter.